A Preliminary Study on the Measurement of Supply Chain Performance: The Determination of Key Performance Indicator (KPI) Weights - Firmansyah, Reza; Budijati, Siti Mahsanah; De’e, Silvia (Journal of Novel Engineering Science and Technology, 2024)
Supply chain performance measurement is crucial in determining strategies to improve company performance. PT XYZ is an export-scale sweet potato-based food processing company. The obstacle the company often faces is the mismatch in the quantity of raw material delivered from suppliers, resulting in delays in production and fulfillment of demand to consumers. For this reason, it is important to measure the performance of the supply chain, so that the company knows the parts of the supply chain that must be improved. Supply Chain Operations Reference (SCOR) is a method for measuring supply chain performance. Before applying the SCOR method, the first step that needs to be done is determining the Key Performance Indicator (KPI) and its weight. This research aims to determine KPI weights using the Analytical Hierarchy Process (AHP) method, at PT XYZ. The AHP method was chosen because of its ability to provide objective weights based on priorities determined by experts. The results showed that there were 6 KPIs at level 1, 19 KPIs at level 2 which were grouped in 6 dimensions, and 50 KPIs at level 3 which were grouped in 19 dimensions. The KPI determination is adjusted to the SCOR dimensions and the real conditions of the company. Furthermore, based on the AHP method analysis, the weight of each KPI is obtained, and the weight comparison between KPIs is known. The implementation of strategies that focus on the KPIs with the highest weights is expected to improve the overall supply chain performance.